Introduction. Cross-Border Inequalities. An Exploration in the Greater Region - Connor, Ulla; Aubry, Lola (Borders in Perspective UniGR-CBS Thematic Issue. Grenzüberschreitende Ungleichheiten in der Großregion | Inégalités transfrontalières dans la Grande Région, 2025)
Keywords: Arbeitnehmer; Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer; Mobilität; Wohnen; Wohnungsmarkt

Grenzüberschreitende Ungleichheiten in der Großregion. Perspektiven und Daten - Himbert, Alexa (Borders in Perspective UniGR-CBS Thematic Issue. Grenzüberschreitende Ungleichheiten in der Großregion | Inégalités transfrontalières dans la Grande Région, 2025)
Abstract: „Seit über 20 Jahren sammelt und analysiert die Interregionale Arbeitsmarktbeobachtungsstelle (IBA·OIE) im Auftrag der politischen Verantwortlichen der Großregion vergleichbare und interpretierbare Daten über den Arbeitsmarkt auf dem Gebiet der Großregion und liefert damit die Grundlage für struktur- und arbeitsmarktpolitische Entscheidungen in der Großregion. Durch die lange und kontinuierliche Beobachtung gelingt es, ein deutliches Bild der Pendlerbewegungen und ihrer Profile im Kooperationsraum der Großregion zu zeichnen und diese engen Verflechtungen sichtbar zu machen. Allerdings werden auch die Unterschiede deutlich, die kulturell bedingt, aber auch durch die heterogenen Wirtschaftsstrukturen der Teilregionen gewachsen sind. Als Grundlage dienen zunächst die Daten der europäischen Statistikbehörde Eurostat, die in harmonisierter Form vorliegen und dadurch im grenzüberschreitenden Kontext leicht vergleichbar sind. Für die detaillierteren Indikatoren auf der Ebene der Großregion werden zudem die Daten der jeweiligen statistischen Ämter und anderer Datenproduzenten aus den Teilregionen herangezogen. Aufgrund unterschiedlicher Hintergründe und Erhebungsmethoden bedürfen die Zahlen einer deutlichen Kontextualisierung und meist einer Harmonisierung. Insbesondere die Daten zu den Grenzgängerströmen stammen aus unterschiedlichen Datenquellen, die einer Harmonisierung auf großregionaler Ebene bedürfen.“
Keywords: Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer

Les travailleurs frontaliers atypiques face aux inégalités transfrontalières. Éclairages et défis - Mezaroş, Mădălina; Uyttebrouck, Constance; Górczyńska-Angiulli, Magdalena; Paccoud, Antoine (Borders in Perspective UniGR-CBS Thematic Issue. Grenzüberschreitende Ungleichheiten in der Großregion | Inégalités transfrontalières dans la Grande Région, 2025)
Abstract: „This article explores the dynamics of atypical cross-border workers in the Greater Region, that is to say, those who reside in a neighbouring country while maintaining employment in Luxembourg. Before highlighting the housing access inequalities that this residential dynamic entails, the analysis examines housing policies in Belgium, France, Germany and Luxembourg to better understand the disparities that intensify pressure on regional housing markets. Recent and historical data on the profiles of atypical cross-border workers are presented, along with testimonies from former residents of Luxembourg who have left the country. The study sheds light on how border housing markets respond to this growing demand, sometimes to the detriment of long-standing residents. It concludes by emphasising the need for a cross-border housing observatory to co-ordinate data collection and assess emerging inequalities, including land pressures and residential exclusion in border areas, calling for more harmonised governance to address these challenges.“
Keywords: Arbeitnehmer; Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer; Wohnen; Wohnungsmarkt

Le travail frontalier au sein de la Grande Région à l’épreuve des frontières depuis les années 1960 - Pigeron-Piroth, Isabelle; Belkacem, Rachid (Hémecht. Zeitschrift für Luxemburger Geschichte = Revue d’histoire luxembourgeoise, 2025)
Abstract: „Within the European Union, the Greater Region Saar-Lor-Lux is the region most impacted by cross-border work. Luxembourg is attracting an increasing number of workers from neighboring countries, mainly from France. This article examines how the practice of cross-border work has evolved over the last sixty years and what the territorial issues are. Rarely taken into account over a long period, the historical dimension is indeed necessary to understand the roots of the phenomenon, its structuring and diversification. The degree of permeability of borders and the reasons for crossing them have changed over time. This analysis provides an overview of cross-border work, focusing on Luxembourg as the main country of employment and Lorraine as the main place of residence for cross-border workers. Contextual factors and different processes - historical, economic, social and political - are important and have encouraged the development of cross-border work in the Greater Region: they have contributed to its institutionalization and to the structuring of the phenomenon. Finally, borders are questioned in the light of emerging territorial challenges, such as labour shortages, the ageing of the population and the resulting tensions pertaining to cross-border work.“
Keywords: Grenzarbeitnehmer

Marché du travail transfrontalier. Différentiels et interdépendances - Pigeron-Piroth, Isabelle; Schiel, Kerry (Borders in Perspective UniGR-CBS Thematic Issue. Grenzüberschreitende Ungleichheiten in der Großregion | Inégalités transfrontalières dans la Grande Région, 2025)
Abstract: „With its 267,300 cross-border workers in 2022, the Greater Region of SaarLorLux is often presented as a model of European integration. Borders are becoming less and less perceptible, and are disappearing for commuters travelling from one country to another. However, the Covid-19 pandemic has shown the reappearance of borders that were thought to have been forgotten. It has to be said that many border-related issues have come to the fore in recent years, all the more so because of the many challenges and tensions as well as the growing number of cross-border workers. The question of inequalities is central in this context of a cross-border labour market with strongly interwoven components.“
Keywords: Arbeitnehmer; Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer

Quelles attitudes et satisfaction envers les moyens de transport? Le cas des frontaliers travaillant au Luxembourg - Gerber, Philippe; Thériault, Marius; Carpentier-Postel, Samuel; Enaux, Christophe (Les travailleurs frontaliers au Luxembourg et en Suisse. Emploi, Quotidien et Perceptions, 2019)
Inhaltstext: „À partir d’une base conceptuelle s’appuyant sur la théorie du comportement planifié développée par Bamberg et Schmidt, l’objectif de cet article est d’estimer, en tant que facteur latent, l’utilité du choix des différents moyens de transport des frontaliers luxembourgeois lors de leurs déplacements domicile-travail, en tenant compte de leurs pratiques et de leurs représentations, tout en ajoutant leur satisfaction relative à ces déplacements. En exploitant une enquête effectuée en 2010-2011, plusieurs modèles d’équations structurales ont été élaborées en prenant en considération l’ensemble de ces éléments. Les résultats principaux du modèle retenu montrent une meilleure estimation du choix modal grâce à la prise en compte de la satisfaction, qui reflète le caractère routinier des trajets quotidiens. Dans notre cas d’étude, le modèle permet également de saisir que les attitudes liées aux moyens de transport ont un meilleur pouvoir explicatif que les attitudes pro-environnementales.“
Keywords: Grenzarbeitnehmer; Verkehr; Verkehrsplanung

Le travail frontalier au Luxembourg. Eléments de contexte et de portrait statistique - Pigeron-Piroth, Isabelle (Les travailleurs frontaliers au Luxembourg et en Suisse. Emploi, Quotidien et Perceptions, 2019)
Inhaltstext: „Au Luxembourg, 44.4% de la main-d’œuvre salariée réside de l’autre côté des frontières et vient des trois pays voisins. Le travail frontalier a des origines anciennes. C’est un phénomène durable, en forte croissance et ancré dans les économies locales. Cette contribution insiste sur l’importance des éléments de contexte dans lesquels se sont développés ces flux et présente les principales caractéristiques, mais aussi les enjeux du travail frontalier au Luxembourg, afin de permettre une mise en perspective avec la Suisse.“
Keywords: Grenzarbeitnehmer

Le travail frontalier au Luxembourg et en Suisse. Similitudes, différences et défis communs - Pigeron-Piroth, Isabelle; Wille, Christian (Les travailleurs frontaliers au Luxembourg et en Suisse. Emploi, Quotidien et Perceptions, 2019)
Keywords: Grenzarbeitnehmer; Schweiz

Cross-border residential mobility of people working in Luxembourg. Developments and impacts - Nienaber, Birte; Pigeron-Piroth, Isabelle (European Borderlands. Living with Barriers and Bridges, 2017)
Keywords: Grenzarbeitnehmer; Sozialraum

Changing Border Regimes. Mining, and Cross-border Labor in the Dutch–Belgian–German Borderlands, 1900–1973 - Knotter, Ad (Journal of Borderlands Studies, 2014)
„In this article the incidence of cross-border commuting to the mining districts in the Belgian–Dutch–German borderlands, known today as the Euregion Meuse-Rhine, will be related to the impact of state borders in different periods. Cross-border labor was closely related to changing border regimes based on uneven economic development, (un)familiarity, and the policy impact of powerful institutions like the state and the church. The main argument is that after the First World War in Dutch Limburg a conscious policy to control the labor force and bind them to mining in the region was relatively successful. Discrepancies in wages and employment opportunities led to border-crossing during restricted periods and for specific groups of workers only.“
Keywords: Grenzarbeitnehmer; Steinkohlenbergbau

The impact of boundaries on cross-border mobility and migration in the Liège-Limburg area (19th–20th centuries) as retrieved from population records - Rutten, Willibrord (Internationales Archivsymposion in Luxemburg (2012). Grenzüberschreitende Migration und Archive. Annalen, mit einem Nachtrag zum Symposion Lüttich (2011) Erster Weltkrieg, 2013)
Keywords: Grenzarbeitnehmer; Steinkohlenbergbau

Grenzüberschreitende Arbeitsmarktpolitik. Institutionen und institutionelle Steuerung des Arbeitsmarktes in der Großregion SaarLorLux-Rheinland-Pfalz-Wallonien - Albrecht, Maria; Meyer, Wolfgang (Grenzüberschreitendes Arbeiten in der Großregion SaarLorLux, 2012)
Keywords: Arbeitsmarkt; Grenzarbeitnehmer; Internationale Mobilität; Saar-Lor-Lux

Transnationale Netzwerke und Institutionen in der Großregion SaarLorLux - Bähr, Holger; Schenke, Hanna; Filsinger, Dieter (Grenzüberschreitendes Arbeiten in der Großregion SaarLorLux, 2012)
Keywords: Arbeitsmarkt; Grenzarbeitnehmer; Internationale Mobilität; Saar-Lor-Lux

Impacts de la mobilité résidentielle transfrontalière sur les espaces de la vie quotidienne des actifs du Luxembourg - Gerber, Philippe; Carpentier-Postel, Samuel (Economie et Statistique, 2012)
Abstract: „À partir d'une enquête effectuée par le CEPS/INSTEAD et la fondation Forum Europa, cet article analyse le phénomène de mobilité résidentielle transfrontalière et son impact sur les déplacements quotidiens. Réalisée au printemps 2008, cette enquête porte sur les actifs occupés résidant initialement au Luxembourg qui se sont installés dans un pays frontalier entre 2001 et 2007, tout en conservant leur emploi au Grand-Duché. Pour un grand nombre d'entre eux, le déménagement transfrontalier a permis d'accéder à un logement plus grand, voire d'en devenir propriétaire. Néanmoins, l'analyse des déplacements quotidiens montre que la grande majorité de ces personnes a dû consentir à de nombreuses concessions en termes de mobilité pour accéder au logement souhaité. Cela se ressent particulièrement pour le trajet domicile/travail dont la distance moyenne a doublé, ce qui a renforcé la dépendance des personnes concernées vis-à-vis de l'automobile. En dehors même du travail, la localisation des autres activités quotidiennes se trouve modifiée à la suite du déménagement. Des indicateurs synthétiques issus de la géostatistique permettent d'analyser la reconfiguration des lieux de ces activités. Malgré la relocalisation de beaucoup d'entre elles autour du nouveau lieu de résidence, une certaine inertie des comportements se traduit par le maintien de près d'une activité sur trois au Luxembourg. Dès lors, la dispersion des espaces d'activités augmente pour certains enquêtés. Cette dispersion, liée à la part des activités transférées vers le pays de résidence, varie fortement selon la nationalité; elle est plus forte pour les Luxembourgeois et pour les Portugais. Les personnes originaires des régions frontalières, qui retournent dans leur pays d'origine, gardent également près d'un quart de leurs activités au Grand-Duché: cela témoigne à la fois de l'importance du lieu de travail dans la structuration des espaces de vie quotidienne et d'un capital spatial déjà mis en évidence dans le cas d'actifs résidant au Luxembourg.“
Keywords: Grenzarbeitnehmer; Mobilität; Sozialraum; Wohnungsmarkt

Grenzüberschreitendes Arbeiten in der Großregion SaarLorLux - Meyer, Jürgen; Rampeltshammer, Luitpold (Universaar, 2012)
Inhaltsverzeichnis: https://d-nb.info/1026984491/04
Keywords: Arbeitsmarkt; Grenzarbeitnehmer; Internationale Mobilität; Saar-Lor-Lux

Lebenslanges Lernen in der Großregion. Grenzenlose Weiterbildung für Pflegekräfte? - Schäfer, Désirée; Renaud, Dagmar; Riemer-Hommel, Petra (Grenzüberschreitendes Arbeiten in der Großregion SaarLorLux, 2012)
Keywords: Altenpflege; Arbeitsmarkt; Berufsbildung; Bildungswesen; Grenzarbeitnehmer; Internationale Mobilität; Krankenpflege

Buitenbeentjes. Nederlandse kompels in de Luikse kolenmijnen na de Tweede Wereldoorlog - Rutten, Willibrord (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2011)
Keywords: Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer; Lüttich; Steinkohlenbergbau

Die grenzüberschreitende Wohnmobilität zwischen Luxemburg und seinen Nachbarregionen - Carpentier, Samuel (Éd. Saint Paul, 2010)
Inhaltsverzeichnis: https://digitale-objekte.hbz-nrw.de/storage/2012/06/19/file_74/4548254.pdf
Keywords: Grenzarbeitnehmer; Pendler

Alsof de taalgrens niet bestond. Limburgse kompels in de Luikse kolenmijnen na de Tweede Wereldoorlog - Rutten, Willibrord (Het Land van Herle. Historisch tijdschrift voor oostelijk Zuid-Limburg, 2009)
Keywords: Grenzarbeitnehmer; Lüttich; Sprachgrenze; Steinkohlenbergbau; Südlimburg (Niederlande)

Goed betaald? Mijnwerkerslonen en arbeidsmarkt in het Nederlands-Duits-Belgische grensgebied in de achttiende en negentiende eeuw - Gales, Ben A. (Jaarboek Van Het Sociaal Historisch Centrum Voor Limburg, 2008)
Keywords: Grenzarbeitnehmer; Steinkohlenbergbau

Regional labour markets and international migration in twentieth-century Europe. The cases of coal mining in Liège (B) and Limburg (NL) compared - Langeweg, Serge; Roels, Leen; Knotter, Ad (Mitteilungsblatt des Instituts für Soziale Bewegungen. Forschungen und Forschungsberichte, 2008)
Keywords: Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer; Lüttich; Steinkohlenbergbau; Südlimburg (Niederlande)

Trekarbeiders en pendelaars. Grensarbeid in oostelijk Zuid-Limburg, 1875–1914 - Langeweg, Serge (Zestig jaar vorsen in de geschiedenis. Jubileumboek Het Land van Herle 1945–2005, 2006)
Keywords: Arbeitsmigration; Grenzarbeitnehmer; Südlimburg (Niederlande)

Historische interacties in de Euregio Maas-Rijn. Migratiestromen in een grensgebied - Korres, Achim (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2002)
Keywords: Arbeitsmigration; Euregio Maas-Rhein; Grenzarbeitnehmer